CBA of cycling. (Nordic Council of Ministers, 2005)
Investing in infrastructure for cycling has a number of effects often not included in ordinary Cost Benefit Analysis, CBA, for roads. It is therefore likely that special methods are needed to conduct CBA for cycling. In February 2005 a Nordic seminar was held in Stockholm. The purpose of the seminar was to share and discuss these Nordic experiences in order to reach a common understanding and platform for further work. The current report summarises the knowledge of CBA of cycling in the Nordic countries and discusses the policy relevance of more advanced methods for cycle infrastructure planning. The report has been compiled by Gunnar Lind.